2014
DOI: 10.3389/fimmu.2013.00501
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Progenitor Origin Distinguishes a Lineage of Dendritic-Like Cells in Spleen

Abstract: The dendritic cell (DC) compartment comprises subsets of cells with distinct phenotypes. Previously this lab reported methodology for hematopoiesis of dendritic-like cells in vitro dependent on a murine splenic stromal cell line (5G3). Co-cultures of lineage-depleted bone marrow (Lin− BM) over 5G3 continuously produced a distinct population of dendritic-like “L-DC” for up to 35 days. Here the progenitor of L-DC is investigated in relation to known BM-derived hematopoietic progenitors. It is shown here that L-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(95 citation statements)
references
References 34 publications
(70 reference statements)
11
84
0
Order By: Relevance
“…After 28 days, co-cultures established with boo/boo Lin - bone marrow yielded significantly higher numbers of both L-DC and cDC-like progeny than WT (Fig 7B). It was previously found that the L-DC progenitor was contained within subsets of LT-HSCs and MPPs [28], while the progenitor of cDC-like cells was contained within CDP and MDP subsets [28]. These results are consistent with evidence for higher numbers of these progenitors in boo/boo over WT bone marrow (Figs 3B and 4B).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…After 28 days, co-cultures established with boo/boo Lin - bone marrow yielded significantly higher numbers of both L-DC and cDC-like progeny than WT (Fig 7B). It was previously found that the L-DC progenitor was contained within subsets of LT-HSCs and MPPs [28], while the progenitor of cDC-like cells was contained within CDP and MDP subsets [28]. These results are consistent with evidence for higher numbers of these progenitors in boo/boo over WT bone marrow (Figs 3B and 4B).…”
Section: Resultssupporting
confidence: 88%
“…A number of studies now equate L-DC progenitors with LT-HSC and MPP subsets in bone marrow, fetal liver, and spleen [26, 28, 38]. In order to compare the prevalence of L-DC progenitors in boo/boo versus WT mice, Lin - bone marrow was prepared and seeded into splenic stromal co-cultures as previously described [27, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods used for antibody staining and flow cytometry for analysis of cell surface marker expression have been described previously [10, 33, 34]. Prior to antibody staining, non-specific antibody binding to cells was inhibited by absorption of anti-CD16/32 (FcBlock: Biolegend: San Diego, CA, USA) used at 5 μg/10 6 cells in 1 mL of FACS buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Previously we showed that “L‐DC” can develop in vitro from hematopoietic stem cells (HSC) overlaid above splenic stroma . During inflammation, the binding of pathogen molecules to Toll‐like receptors (TLR) on HSC can trigger differentiation .…”
Section: Resultsmentioning
confidence: 99%